Complimentary Feeding Practices in Under-2 Children (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: Complimentary feeding (CF) practices are quiet frustating in our country. Innaproprite foods in first two years of life have detrimental impact on health and growth of children. The aim of the study was to see the present pattern of CF practices, to identify wrong practices and to  develop awareness among medical professionals so that they may encourage appropriate practices more vigorously for reducing child mortality and morbidity.Methods: A cross-sectional study was conducted from October, 2011 to December, 2011 in the Pediatric department (indoor and outdoor) of Sir Salimullah Medical College Mitford Hospital, Dhaka and in a private chamber of a district town of Bangladesh. Four hundred motherchild pairs were selected by non-random convenience sampling method. 6-24 months old children and children under six months (if was on complimentary feeding) were included. Data was collected from the mothers/caregivers of the children in a pretested semi-structured data collection sheet and analyzed by SPSS version 12. Appropriate statistical tests were done. Statistical significance was considered if p value was